Ambient Marketing Practices in the United States: A Professional View - Amiee J. Shelton; Łukasz P. Wojciechowski; Jamie Warner (Communication Today, 2025)
Although ambient communication has been of particular interest to both marketers and advertising agencies over the last several years, there is a paucity of academic research concerning ambient media usage. Academic research is limited to traditional outdoor advertising, specifically investigating billboards and outdoor and point-in-time examples of ambient success. This present study investigates the use of ambient marketing strategies by professionals in the various fields that make up marketing communication in order to fill a void in the existing literature. Overall, this study provides clarity regarding how marketing and public relations professionals (i.e. professional communicators) consider ambient media practices as a strategy for overall communication efforts. This qualitative study investigated the attitudes and feelings of marketing and public relations professionals regarding the use of ambient marketing practices. Findings stem from 39 in-depth interviews with communication professionals in the New England region of the United States. Analysis reveals a detailed picture showing that professional communicators are not completely knowledgeable about the term “ambient” but are generally knowledgeable about non-traditional types of marketing techniques. We found that the degree of attitudes, knowledge and use varied between specific disciplines within the professional communication field, and as well as between the age levels of participants. This study may form the basis for survey-based studies investigating the specific variables inherent in ambient media usage.